UV-assisted size sampling and antibacterial screening of lantana camara leaf extract synthesized silver nanoparticles - Singh, Pradeep Kumar; Bhardwaj, Kirti; Dubey, Parul; Prabhune, Asmita (RSC Advances, 2015)
Green route synthesized silver nanoparticles are extremely toxic to multidrug resistant bacteria and have widespread applications in biomedical science. If the silver reducing weed extract possesses antimicrobial properties then it can additionally contribute to the medicinal activity. Herein, we present a synthesis of silver nanoparticles by using the weed plant Lantana camara's leaf extract. This study shows an easy, quick and cost-effective route to silver nanoparticle synthesis. Size controlled synthesis of Ag-0 nanoparticles is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, infrared spectroscopy, X-ray diffraction measurements, FE-SEM and TEM analysis. The synthesis of silver nanoparticles via this green approach shows very high antibacterial activity against E coli (Gram -ve) and S. aureus (Gram +ve) bacteria at a very low concentration (50 ppm Ag nanoparticles). Use of such eco-friendly nanoparticles may open a door for a new range of bactericidal agents.